Kajian Proses Penciptaan Karya Kolaboratif The Bayan Tale Seniman Erwin Windu Pranata Di Artjog Kids 2023 - Afandi, Nizar Mohamad; Sucitra, I Gede Arya; Witjaksono, Bambang (Institut Seni Indonesia Yogyakarta, 2025)
This study analyzes the creation process of the collaborative participatory artwork The Bayan Tale by artist Erwin Windu Pranata at ARTJOG KIDS 2023. The research aims to understand how the concept of collaborative art was implemented in a project involving children. Using a qualitative-descriptive method, data was collected through participant observation, in-depth interviews, and document analysis, framed by theories of participatory culture, relational, and dialogical aesthetics. The findings show that the project was a manifestation of ARTJOG's vision of inclusivity and Erwin's artistic practice. The creative process featured a dynamic spectrum of participation: children had high agency in the ideation and performative activation stages, while the artist maintained technical and curatorial control. The artist acted as a facilitator and